Comparative analysis of the basic features of the expected and perceived quality of mass passenger public transport service in Belgrade - Filipović, Snežana; Tica, Slaven; Živanović, Predrag; Milovanović, Branko (Transport, 2009)
Recently, negative trends towards the environment where the system of Mass Passenger Public Transport (MPPT) operates continue to grow. Mobility and citizens’ standard of living are constantly increasing. A significant increase in using private cars (level of motorization) along with all negative consequences faced under such circumstances as an increase in traffic volume, congestions, a decrease in travelling speed, a higher number of traffic accidents, greater negative influence on the environment etc. can be noticed. The city of Belgrade has recognized the significance of continuous research and has monitored the quality of Mass Passenger Public Transport service as well as changes that are taking place in order to influence some specific parts of transport and traffic policy in the city. This paper contains the benchmarking of results obtained in research and a trend towards changes in the expected and perceived quality of service (QoS) within the system of Mass Passenger Public Transport in Belgrade within the period from 2005 to 2007.First published online: 27 Oct 2010